FOOD HABITS CHANGES AND ITS EFFECT ON HEALTH OF PEOPLE OF VALSAD, GUJARAT DURING COVID-19 PANDEMIC - PATEL DHWANI MUKESHBHAI (International Journal of Innovations in Engineering Research and Technology, 2021)
A new coronavirus emerged in Wuhan, China as a pandemic of acute respiratory syndrome in humans in December 2019. In India the virus COVID- 19 spread in February – March. Till from now [3rd September 2020] the total confirmed cases of corona are around 5.21 M. The Prime Minister of India Narendra Modiji declared complete lockdown of India in different phases from 25th March 2020 to 31 May 2020. Aside from more snacking, the pandemic has changed what people are eating, a higher percentage of people said that they were eating healthier than they usually do, as a result of the pandemic. And this was compared to a lower percentage of people who said that they were eating less healthy than usual. As related to COVID-19 people were taking the opportunity to be thinking more about what they were eating, perhaps. Cooking more at home tends to be a little bit healthier than the choices that we might make when eating out. The COVID -19 pandemic represents a massive impact on human health, causing sudden lifestyle changes, through social distancing and isolation at home, with social and economic consequences optimizing public health during this pandemic requires not only knowledge from the medical and biological sciences, but also of all human sciences related to lifestyle, social and behavior studies, including dietary habits and lifestyle.